2016
DOI: 10.1021/acsami.6b11767
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-Based Molecular Trap as an Evanescent Wave Infrared Chemical Sensing Medium for the Selective Determination of Amines in Air

Abstract: An evanescent wave infrared chemical sensor was developed to selectively detect volatile amines with heterocyclic or phenyl ring. To achieve this goal, a rhenium-based metallacycle with a "molecular-trap" structure was designed and synthesized as host molecules to selectively trap amines with heterocyclic or phenyl ring through Re-amine and π-π interactions. To explore the trapping properties of the material, a synthesized Re-based molecular trap was treated on an IR sensing element, and wide varieties of vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, the transparent ZnTPPS/C10S/LDH film was capable of detecting pyridine at low concentrations in the order of µmol per litre. In addition, it was found that the pyridine detection sensitivity of the transparent ZnTPPS/C10S/LDH film in the aqueous solution did not reach that of the Re-based molecular trap (i.e., 72 nmol/L) employing an evanescent wave infrared chemical sensing method, which is recognized as a high-sensitivity detection method, and was reported by Huang et al 21 However, the pyridine detection sensitivity of the transparent ZnTPPS/C10S/LDH film in the aqueous solution was significantly higher than those of the ZnS nanoparticles reported by Li et al (6.76 × 10 −5 mol/L) 22…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the transparent ZnTPPS/C10S/LDH film was capable of detecting pyridine at low concentrations in the order of µmol per litre. In addition, it was found that the pyridine detection sensitivity of the transparent ZnTPPS/C10S/LDH film in the aqueous solution did not reach that of the Re-based molecular trap (i.e., 72 nmol/L) employing an evanescent wave infrared chemical sensing method, which is recognized as a high-sensitivity detection method, and was reported by Huang et al 21 However, the pyridine detection sensitivity of the transparent ZnTPPS/C10S/LDH film in the aqueous solution was significantly higher than those of the ZnS nanoparticles reported by Li et al (6.76 × 10 −5 mol/L) 22…”
Section: Resultsmentioning
confidence: 88%
“…synthesized via the NaCl/acetate-buffer decarbonation and anion-exchange methods in the presence of PrONa, as described in the literature. 21 The transparent LDH film bearing carbonate anions (transparent CO 3 2− -LDH film) was prepared by applying the filtration-film transfer method to an aqueous dispersion of LDH nanosheets (total volume: 2 mL, LDH particle concentration: 0.15 mg/L) according to our previous report. 19 The transparent LDH film bearing perchlorate anions (transparent Initially, the dried transparent ZnTPPS/C10S/LDH film was immersed in aqueous pyridine solutions of various concentrations ([Pyridine] = 0-0.123 mol/L) for 2 min (step 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the preparation of MMIPs by molecularly-imprinted surface polymerization, template molecule and functional monomers were pre-assembled to form relatively stable hydrogen bonds [32]. According to the structure of triazophos, it can form hydrogen bonds with compounds containing carboxyl groups, hydroxyl groups, and pyridine rings, and π-π conjugation builds up to form heterocyclic complexes [33]. Hence, the choice of functional monomers is a key factor in the formation of specific binding sites, particularly in non-covalent MMIPs.…”
Section: Resultsmentioning
confidence: 99%